2021
DOI: 10.3390/agronomy11050975
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Biosynthesis in Hairy Root Cultures of Tan and Purple Seed Coat Peanuts

Abstract: Peanut (Arachis hypogaea) is a crop that can produce resveratrol, a compound with various biological properties, such as those that exert antioxidant, anticancer, and anti-inflammatory effects. In this study, trans-resveratrol was detected in the roots, leaves, and stems of tan and purple seed coat peanuts (Arachis hypogaea) cultivated in a growth chamber. Both cultivars showed higher levels of resveratrol in the roots than the other plant parts. Thus, both cultivars were inoculated with Agrobacterium rhizogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…After induction by B. thuringiensis TG5 and carbendazim, peanut plants secrete glutamyl-s-cysteine sulfoxide and 4,8-dimethyldeca-4,8-dieonic acid, respectively, as defense means. Some bioactive compounds in peanuts ( Kuei et al, 2021 ; Park et al, 2021 ; Duke, 2022 ; Li et al, 2022 ), including resveratrol ( Luo et al, 2021 ; Zhu et al, 2022 ), β-sitosterol, proanthocyanidin, linoleic acid and arachidonic glycosides have inhibitory effects on plant pathogenic bacteria and fungi. To further explore the metabolic pathway and mechanism of microbial pesticides inducing peanut disease resistance, and the difference in disease resistance between microbial pesticides and traditional chemical pesticide carbendazim, provide data and theoretical support for the development and promotion of microbial pesticides, which is of great practical significance for sustainable agricultural development.…”
Section: Discussionmentioning
confidence: 99%
“…After induction by B. thuringiensis TG5 and carbendazim, peanut plants secrete glutamyl-s-cysteine sulfoxide and 4,8-dimethyldeca-4,8-dieonic acid, respectively, as defense means. Some bioactive compounds in peanuts ( Kuei et al, 2021 ; Park et al, 2021 ; Duke, 2022 ; Li et al, 2022 ), including resveratrol ( Luo et al, 2021 ; Zhu et al, 2022 ), β-sitosterol, proanthocyanidin, linoleic acid and arachidonic glycosides have inhibitory effects on plant pathogenic bacteria and fungi. To further explore the metabolic pathway and mechanism of microbial pesticides inducing peanut disease resistance, and the difference in disease resistance between microbial pesticides and traditional chemical pesticide carbendazim, provide data and theoretical support for the development and promotion of microbial pesticides, which is of great practical significance for sustainable agricultural development.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hairy roots have been obtained from many plant sources for the production of most groups of secondary metabolites, including phenolics, alkaloids, glucosinolates, terpenoids, and others. Many previous studies have confirmed that hairy roots can be a good source of plant-derived bioactive compounds, with flavonoid (anthocyanin) accumulation in hairy roots of Fagopyrum tataricum [ 17 ], flavone accumulation in hairy roots of Scultellaria baicalensis [ 18 ], ginsenoside production in hairy roots of Platycodon grandiflorum [ 19 ], glucosinolate production in hairy roots of Nasturtium officinale [ 20 ], resveratrol in hairy roots of Arachis hypogaea [ 21 ], tropane alkaloids in hairy roots of Hyoscyamus reticulatus [ 22 ], and tanshinone in hairy roots of Salvia miltiorrhiza [ 23 ].…”
Section: Introductionmentioning
confidence: 99%